2022
DOI: 10.1371/journal.pone.0271205
|View full text |Cite
|
Sign up to set email alerts
|

Radiation therapy enhances systemic antitumor efficacy in PD-L1 therapy regardless of sequence of radiation in murine osteosarcoma

Abstract: Recent studies demonstrate that immune checkpoint blockade (ICB) increases the chances of the abscopal effect, an anti-tumor effect outside the radiation field in radiation therapy. However, the optimal sequence between radiation and ICB remains unclear. To investigate the impact of sequence of radiation in anti-PD-L1 antibody (P1) therapy on immune microenvironments and antitumor efficacies in local and abscopal tumors, metastatic LM8 osteosarcoma cells were inoculated into both legs of C3H mice. For irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In 2018, Xia et al (2018) first reported that in a mouse model, radiotherapy could enhance the efficacy of PD-1 inhibition on brain metastatic OS, increasing the number of CD8 + T cells in the TME. Katsuki et al (2022) alfound a similar outcome of combination therapy in a mouse OS model. Callaghan et al (2020) combined pembrolizumab with stereotactic body radiation to treat chondroblastic OS.…”
Section: New Therapeutic Methodsmentioning
confidence: 83%
“…In 2018, Xia et al (2018) first reported that in a mouse model, radiotherapy could enhance the efficacy of PD-1 inhibition on brain metastatic OS, increasing the number of CD8 + T cells in the TME. Katsuki et al (2022) alfound a similar outcome of combination therapy in a mouse OS model. Callaghan et al (2020) combined pembrolizumab with stereotactic body radiation to treat chondroblastic OS.…”
Section: New Therapeutic Methodsmentioning
confidence: 83%
“…In the past decade, the ICB immunotherapies has achieved positive response in osteosarcoma patients [ 10 ]. However, only a small proportion of osteosarcoma patients can respond to immunotherapies, and the major reason might be the limitations in their tumor immunity status [ 15 ]. To verify whether MGR was capable of predicting the efficiency of anti-cancer immunotherapies in osteosarcoma patients, we analyzed the expression levels of immunomodulators (HAVCR2, LAG3, CTLA4, PDCD1, GZMA, NKG7, GZMM, IFNG) were significantly increased in low-risk group than high-risk group of TRAGET dataset and GSE21257 dataset.…”
Section: Discussionmentioning
confidence: 99%
“…This was translated in clinical settings with a case report of a patient with small-cell lung carcinoma who was treated with a combination of radiation therapy and nivolumab [ 56 ]. In murine osteosarcoma, radiotherapy could enhance antitumor efficacy of anti-PD-L1 treatment with a significant decrease in tumor growth and an improved overall survival via an increase in PD-1-positive and granzyme B-positive CD8+ T cells [ 57 ].…”
Section: Strategies To Turn Non-inflamed Cold Tumors Into Inflamed Ho...mentioning
confidence: 99%